THE NEEDS ANALYSIS OF SENIOR HIGH SCHOOL STUDENTS’ READING COMPETENCE IN NATIONAL EXAMINATION: STUDENTS’ PERSPECTIVE - ari mayang; Joko Nurkamto; Nur Arifah Drajati (ETERNAL (English, Teaching, Learning and Research Journal), 2019)
The focus of this research is to asses the Reading competence needs of senior high school students in English National Examination (ENE) based on students’ perspective. The background in conducting this research mainly because of two things. The first one is the importance of curriculum evaluation behind the Needs Analysis itself. The  second one is the importance of the certain preparation for strengthening English material to face the English National Examination. Both of these backgrounds are equally important for students and teachers at once. The research questions of this study are framed within the scope of students’ perspective. The method of this research included some of questionnaires which was then analyzed using the five-points Likert Scale method. This research already debriefed 106 senior high school students in grade 12 from Boyolali regency, Central Java. They were involved in filling out the questionnaire where the results were used as the main data in this study. The final findings in this study include the fact that: (1) The Reading questions in National Examination are in moderate level of difficulty based on the students perspective, (2) The Reading National Examination materials are clearly taught by the teachers, (3) Reading is very important material to be mastered in National Examination, (4) The students are in moderate level dealing with their mastery of Reading material in National Examination, (5) The use of technology in Reading material learning is very important method based on students’ perception, and (6) The frequency of use of technology in Reading lessons by teachers is quite often (moderately) based on student opinions.